2006
DOI: 10.1002/adsc.200606125
|View full text |Cite
|
Sign up to set email alerts
|

New Recoverable Poly(ethylene glycol)‐Supported C1Diamino‐oligothiophene Ligands for Palladium‐Promoted Asymmetric Allylic Alkylation (AAA) Reactions

Abstract: A new class of chiral C 1 -symmetrical diamino-oligothiophene ligands easy-grafted on a soluble polymeric support (MeOPEG 5000 ) is described. The diamines were found to be effective promoting agents for the [Pd(0)]-catalysed asymmetric allylic alkylation (AAA) of dimethyl malonate in high yields and excellent enantioselectivity (ee up to 99 %). The supported chiral ligand was readily recovered by precipitation and filtration was recycled up to three times without an appreciable loss in activity. The recycle o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…During our ongoing research focused on the stereoinductive properties of C 2 -symmetric diaminobithiophenes (DAT2, 1 , Figure ) 6 in metallo-catalyzed transformations, we demonstrated that the combination of 1 with Cu(OAc) 2 8 (0.1−5 mol %) smoothly promoted the condensation of nitromethane with a variety of aldehydes in excellent enantiomeric excess . The ready synthetic accessibility and facile manipulation of thiophene-based compounds allowed us to prepare in few steps a C 1 -symmetric DAT2 analogue tethered to poly(ethylene glycol) (MeO-PEG 5000 , 2 , Figure )that was effectively employed in Pd-catalyzed asymmetric allylic alkylations. Here, the recovery of the supported ligand for several runs without any loss of activity was demonstrated.…”
mentioning
confidence: 99%
“…During our ongoing research focused on the stereoinductive properties of C 2 -symmetric diaminobithiophenes (DAT2, 1 , Figure ) 6 in metallo-catalyzed transformations, we demonstrated that the combination of 1 with Cu(OAc) 2 8 (0.1−5 mol %) smoothly promoted the condensation of nitromethane with a variety of aldehydes in excellent enantiomeric excess . The ready synthetic accessibility and facile manipulation of thiophene-based compounds allowed us to prepare in few steps a C 1 -symmetric DAT2 analogue tethered to poly(ethylene glycol) (MeO-PEG 5000 , 2 , Figure )that was effectively employed in Pd-catalyzed asymmetric allylic alkylations. Here, the recovery of the supported ligand for several runs without any loss of activity was demonstrated.…”
mentioning
confidence: 99%
“…In 2006, Bandini and Benaglia described the syntheses of PEG 5000 -bound DATs 24a and b using eq 28 and used the PEG-bound catalysts for palladium promoted asymmetric alkylation of allylic esters with dimethylmalonate (eq 29). …”
Section: Solid/liquid Separations Of Soluble Polymer-bound Ligands An...mentioning
confidence: 99%
“…If the reaction mixture was passed through Celite, only the ligand was recovered. The batches were refilled with palladium to improve the recyclability allowing up to three cycles with minimal ee erosion …”
Section: Asymmetric Allylic Substitutionmentioning
confidence: 99%
“…The batches were refilled with palladium to improve the recyclability allowing up to three cycles with minimal ee erosion. 615…”
Section: Homogeneous Catalystsmentioning
confidence: 99%